Understanding particle formation in surfactant-free waterborne coatings prepared by emulsification of pre-formed polymers. Issue 19 (12th April 2017) - Gonzalez-Alvarez, Maria Jose; Paternoga, Jan; Breul, Katharina; Cho, Hyungjun; Roshandel, Mahtab Z.; Soleimani, Mohsen; Winnik, Mitchell A.
Abstract : Concern for the environment has been driving major changes in the coatings industry. Abstract : Concern for the environment has been driving major changes in the coatings industry. To reduce the amount of volatile organic compounds (VOC's) released to the atmosphere; new technology and deeper understanding should be developed to replace solvent-based coatings with water-based coatings. Most of these coatings contain latex particles prepared by emulsion polymerization, referred to as primary dispersions. Secondary dispersions are polymer nanoparticles in water normally prepared by nanoprecipitation in water of pre-formed polymer dissolved in a water-miscible organic solvent, which is later removed. In this work we design a new approach to secondary dispersions involving direct emulsification of a solid carboxylated polymer prepared by a solvent-free process. We carry out experiments to understand the emulsification process including polymer exchange among nanoparticles as the dispersions in water are annealed. We used a low molecular weight acid-functional styrene-acrylic copolymer (nominal M n 5000 g mol −1, Đ = 3). With this polymer, we prepared aqueous polymer dispersion through partial neutralization with ammonia and vigorous stirring in hot water, in the absence of any organic solvent or surfactant. We labelled samples of the polymer with donor and acceptor dyes, which enabled us to study mixing of polymer molecules by fluorescence resonance energy transfer (FRET) during emulsification and upon annealing the dispersions. Our goal with labelling the polymer is to investigate the dispersion process as the partially neutralized polymer is stirred and heated, and to understand aspects of the colloidal stability of the dispersion at ambient and elevated temperatures. These types of polymers have the potential to serve as the basis for environmentally friendly tough and robust thermoset paints and coatings.